THE INFLUENCE OF TIME MANAGEMENT AND COLLEGE MOTIVATION ON ACADEMIC ACHIEVEMENT IN STUDENTS MAJORING IN MANAGEMENT WHO ARE WORKING AT THE TERBUKA UNIVERSITY OF UPBJ JAKARTA - Kukuh Wahyu Hadi Dian Wijaya; Ibnu Farid (OIKONOMIA: Journal of Economics and Management Science, 2024)
This research aims to evaluate the influence of time management and college motivation for academic achievement in self - employed students who are working at Terbuka Univeristy. The hypothesis is that time management and college motivation have a positive and significant influence on the academic achievement of working students .Method study Which used is quantitative with collection data via a Google Form quiz Technique taking sample Which used is Non Probability Sampling , with a focus on self-employed students who are currently working and are in the 6th semester and above. The number of samples used was 100 respondents.The results of analysis using SPSS software show that the two variables , time management and college motivation , have a positive and significant influence towards academic achievement , with a value of significance that is smaller than the specified limit .Simultaneously , these two variables also jointly influence academic achievement .In addition , the results of the national coefficient of determination test show that 60.4 % of the variation in ability in the academic achievement of self - employed students can be explained . by time management and motivation . The rest as big as 39.6%, I explain by other factors not researched in this model .Thus , this research contributes to the understanding of the factors that influence the academic achievement of self - employed students , as well as providing a basis for preparing strategies to improve academic achievement in the context of learning conditions while working